SUPPLY CHAIN DISRUPTIONS AND CAPITAL RESILIENCE IN THE NIGERIAN AGRICULTURAL INDUSTRY (UNIZIK Journal of Marketing, 2025)
This study investigated how supply chain disruptions impact capital resilience in Nigeria's agricultural sector, focusing on three dimensions namely, supply chain orientation, risk management, and resource configuration capabilities. Using a cross-sectional survey design, data were collected from 369 employees across production, procurement, logistics, marketing, and warehousing departments of Okomu Oil Plc and Presco Plc in Benin City. The study used the questionnaire as an instrument to elicit primary data from the respondents. The reliability of each questions for each variables were ascertained with chroncba alpha values, 0.84, 0.83, 0.92 and 0.86 respectively. Descriptive and inferential statistics were employed for analysis. Findings reveal that supply chain orientation and risk management significantly enhance capital resilience by improving integration, coordination, and proactive risk mitigation. However, resource reconfiguration capabilities showed no significant impact, suggesting flexibility alone is insufficient without broader strategic alignment. The study recommends strengthening supply chain collaboration, visibility, and redundancy to bolster resilience. Additionally, firms should invest in robust risk management frameworks, including regular assessments and contingency planning, to mitigate disruptions effectively. These insights highlight the importance of holistic supply chain strategies in Nigeria’s consumer goods sectors, emphasizing proactive measures over reactive resource adjustments.
Keywords: Supply Chain Disruptions, Organizational Resilience, Risk Management, Strategic Resilience, Capital Resilience, Relationship Resilience